Post‐transplantation diabetes mellitus: evaluation of treatment strategies. (May 2015) - Haidinger, M.; Antlanger, M.; Kopecky, C.; Kovarik, J.J.; Säemann, M.D.; Werzowa, J.
Abstract Background Post‐transplantation diabetes mellitus (PTDM) is a serious complication after kidney transplantation, but evidence regarding long‐term outcomes of treatment regimens remains scarce. Aim and Methods The aim of this retrospective cohort analysis was to assess the long‐term efficiency and safety of antidiabetic treatments in kidney transplant recipients (KTRs), who were diagnosed with PTDM by an oral glucose tolerance test (OGTT). Results Of 561 KTRs that were screened for PTDM at our outpatient clinic, 71 (13%) had a diabetic OGTT and were included in this study. Mean follow‐up was 34.2 ± 16.1 months. Thirty‐six PTDM patients (51%) received antidiabetic treatment after diagnosis with either a dipeptidyl peptidase‐4 (DPP‐4) inhibitor, a sulfonylurea, pioglitazone, or insulin. These patients had significantly higher fasting glucose and two‐h plasma glucose (2HPG) values at baseline than those who remained without therapy. In contrast to lifestyle modification alone or sulfonylureas, DPP‐4 inhibitors improved glycemic control significantly. Adverse events were generally mild and occurred at similar rates in all groups. Conclusion While sulfonylureas failed to improve glycemic control, DPP‐4 inhibitors appeared effective and safe for the therapy of PTDM after kidney transplantation.